Social Work, Social Politics and Justice - Heinz Sünker (Social Work and Society)
"The disaster does not primarily lie in people and in the way that they perceive the circumstances, rather in the circumstances that doom people to powerlessness and apathy - circumstances which they could, however, change" (Adorno, 1966, p. 189). When Karl Marx writes to Friedrich Sorge in his letter of the 19.10.1877, regarding his critique of the opinion of his opponents Dühring & Co., that one must deal with "a whole crowd of immature students and pompous doctors who claim to give socialism a 'higher, ideal' turn, that is to say, to replace the materialistic basis (that demands serious, objective study if one wants to operate on it)"¦ with modern mythology by means of their goddesses of justice, freedom, equality and fraternité" (Marx, 1973, p. 303; cf. Schiller, 1993, p. 199 onwards), this thus refers to fundamental problems with the concept of "justice" up until today. As the debate shows, it concerns the contextualization of the term "justice", its meaning in historically concrete as well as socio-political circumstances, and therefore a social analysis that is both representation and critique. Essentially it also concerns the question of the relationship between ideas and reality and the development of standards of historical systematic 'nature' out of social frameworks (see Frey, 1978; Theunissen, 1989).